PENGARUH LEADER MEMBER EXCHANGE TERHADAP KEPUASAN KERJA KARYAWAN - Harahap, Rizka Nurhasti Agusta; Amalia, Sholihati (POLITEKNIK NEGERI BANDUNG, 2016)
Leaders have a responsibility to manage human resources. Thus it is necessary a good relationship between the leader and the employee support the achievement of organizational goals. But in fact, indirectly leaders give higher trust to some employee only and does not do justice to any of his employees. Therefore, the employees may feel dissatisfied with their jobs because they feel unappreciated or unnoticed. It became one of the reasons the employees resign. On 2015 the number of employees who resigned from PT Sandy Globalindo is big enough. It is certainly become a problem for the company and could adversely affect the sustainability of the company. This research aims to determine the influence of leader-member exchange to employee job satisfaction in PT Sandy Globalindo. Leader-member exchange is variable (X) and job satisfaction is a variable (Y). The research method that used is the analytic method with cross sectional approach. Analysis of the data that used is descriptive analysis, classic assumption test, regression test, correlation and hypothesis test. The sample in this research as many as 101 employees. Descriptive analysis showed that the leader-member exchange in PT Sandy Globalindo in the category enough with a mean of 2.91 and job satisfaction of employees at PT Sandy Globalindo in the category enough with a mean of 3.04. Simple linear regression test results, obtained equation Y = 3.681 + 0.382 0,759X with R square which indicates that the variable leader-member exchange impact of 38.2% on job satisfaction while amounting to 61.8% of job satisfaction influenced by other things that are not explained in this research. Therefore, it can be concluded that there is significant influence of leader-member exchange to employee job satisfaction in PT Sandy Globalindo.